Medical surveillance programme for diisocyanate exposure. Issue 4 (15th October 2010) - Labrecque, Manon; Malo, Jean-Luc; Alaoui, Khadija M; Rabhi, Khalil
Abstract : Objectives: Surveillance programmes for occupational asthma should reduce the severity of asthma both at the time of diagnosis and after removal from exposure as well as costs related to functional impairment. The aim of this study was to compare the severity and cost of diisocyanate-induced occupational asthma in workers participating in a surveillance programme and in twice the number of workers diagnosed after being referred by their physician. Methods: Answers to a self-administered questionnaire led to possible referral for further assessment that included methacholine testing and specific inhalation challenges as the gold standard for confirming occupational asthma. Results: Of the 2897 workers who participated, 182 (6.3%) had a positive questionnaire. 79/182 (43%) were referred for further medical assessment and 20 had confirmed occupational asthma by specific inhalation testing. At the time of diagnosis, the 20 screened subjects had a mean PC20 of 3.35 mg/ml as compared to 1.50 mg/ml (p=0.05) in the 66 controls. Two years after diagnosis and removal from exposure, the 20 subjects screened had a mean PC20 of 4.81 mg/ml compared to 1.67 mg/ml (p=0.03) in controls. Clinical remission occurred in 34% of the screened group compared to 16% of the control group (p=0.02). The median costs for functional impairment were $C11 900 in screened subjects and $C19 600 in controls (p=0.04). Conclusions: Subjects with occupational asthma screened by a medical surveillance programme have a better outcome both at the time of diagnosis and 2 years after removal from exposure, with lower compensation costs compared to controls.